China's Rangeland Management Policy Debates: What Have We Learned? - Gongbuzeren; YanBo Li; Wenjun Li (Rangeland Ecology & Management, 2015)
In China, three major rangeland management policies have caused dramatic social, economic, and ecological changes for pastoral regions in the past 30 yr: the Rangeland Household Contract Policy (RHCP), Rangeland Ecological Construction Projects (RECPs), and the Nomad Settlement Policy (NSP). The impacts of these policies are greatly debated. In this paper, we conduct a systematic review of academic perspectives on the impacts of the three policies and the causes of ineffective and negative effects. The findings demonstrate that academics increasingly report negative impacts of RHCP on the ecosystem, animal husbandry, pastoralist livelihoods, and pastoral society. An increasing number of scholars, although not the majority, attribute the negative impacts to improper policy itself rather than incomplete implementation. Regarding the RECPs, most academics believe that policies have improved the rangeland ecosystem but with obvious negative impacts on pastoralist livelihoods and pastoral society; they attribute the problems to incomplete policy implementation. For the NSP, most academics report positive impacts on pastoralist livelihoods and animal husbandry, although recent researchers have identified negative impacts on pastoral society and the ecosystem. Although they are not in the mainstream, more and more academics attribute the negative impacts to improper policy. Finally, we apply the concept of coupled social-ecological systems (SES) to further analyze the outcomes of these three policies and propose a more flexible and inclusive land tenure policy that recognizes the diverse local institutional arrangements; an integrated RECP framework that considers coadaptation between social and ecological systems; and facilitating voluntary choice in nomad settlement and developing innovative approaches to provide social services for pastoralists who would like to remain in pastoral areas. As these three policy approaches are applied in rangeland management and pastoral development worldwide, this paper may provide useful implications for future policy development in pastoral regions on a global scale. (C) 2015 Society for Range Management. Published by Elsevier Inc. All rights reserved.;ABSTRACT In China, three major rangeland management policies have caused dramatic social, economic, and ecological changes for pastoral regions in the past 30 yr: the Rangeland Household Contract Policy (RHCP), Rangeland Ecological Construction Projects (RECPs), and the Nomad Settlement Policy (NSP). The impacts of these policies are greatly debated. In this paper, we conduct a systematic review of academic perspectives on the impacts of the three policies and the causes of ineffective and negative effects. The findings demonstrate that academics increasingly report negative impacts of RHCP on the ecosystem, animal husbandry, pastoralist livelihoods, and pastoral society. An increasing number of scholars, although not the majority, attribute the negative impacts to improper policy itself rather than incomplete implementation. Regarding the RECPs, most academics believe that policies have improved the rangeland ecosystem but with obvious negative impacts on pastoralist livelihoods and pastoral society; the.;  In China, three major rangeland management policies have caused dramatic social, economic, and ecological changes for pastoral regions in the past 30yr: the Rangeland Household Contract Policy (RHCP), Rangeland Ecological Construction Projects (RECPs), and the Nomad Settlement Policy (NSP). The impacts of these policies are greatly debated. In this paper, we conduct a systematic review of academic perspectives on the impacts of the three policies and the causes of ineffective and negative effects. The findings demonstrate that academics increasingly report negative impacts of RHCP on the ecosystem, animal husbandry, pastoralist livelihoods, and pastoral society. An increasing number of scholars, although not the majority, attribute the negative impacts to improper policy itself rather than incomplete implementation. Regarding the RECPs, most academics believe that policies have improved the rangeland ecosystem but with obvious negative impacts on pastoralist livelihoods and pastoral society; they attribute the problems to incomplete policy implementation. For the NSP, most academics report positive impacts on pastoralist livelihoods and animal husbandry, although recent researchers have identified negative impacts on pastoral society and the ecosystem. Although they are not in the mainstream, more and more academics attribute the negative impacts to improper policy. Finally, we apply the concept of coupled social-ecological systems (SES) to further analyze the outcomes of these three policies and propose a more flexible and inclusive land tenure policy that recognizes the diverse local institutional arrangements; an integrated RECP framework that considers coadaptation between social and ecological systems; and facilitating voluntary choice in nomad settlement and developing innovative approaches to provide social services for pastoralists who would like to remain in pastoral areas. As these three policy approaches are applied in rangeland management and pastoral development worldwide, this paper may provide useful implications for future policy development in pastoral regions on a global scale.;In China, three major rangeland management policies have caused dramatic social, economic, and ecological changes for pastoral regions in the past 30yr: the Rangeland Household Contract Policy (RHCP), Rangeland Ecological Construction Projects (RECPs), and the Nomad Settlement Policy (NSP). The impacts of these policies are greatly debated. In this paper, we conduct a systematic review of academic perspectives on the impacts of the three policies and the causes of ineffective and negative effects. The findings demonstrate that academics increasingly report negative impacts of RHCP on the ecosystem, animal husbandry, pastoralist livelihoods, and pastoral society. An increasing number of scholars, although not the majority, attribute the negative impacts to improper policy itself rather than incomplete implementation. Regarding the RECPs, most academics believe that policies have improved the rangeland ecosystem but with obvious negative impacts on pastoralist livelihoods and pastoral society; they attribute the problems to incomplete policy implementation. For the NSP, most academics report positive impacts on pastoralist livelihoods and animal husbandry, although recent researchers have identified negative impacts on pastoral society and the ecosystem. Although they are not in the mainstream, more and more academics attribute the negative impacts to improper policy. Finally, we apply the concept of coupled social-ecological systems (SES) to further analyze the outcomes of these three policies and propose a more flexible and inclusive land tenure policy that recognizes the diverse local institutional arrangements; an integrated RECP framework that considers coadaptation between social and ecological systems; and facilitating voluntary choice in nomad settlement and developing innovative approaches to provide social services for pastoralists who would like to remain in pastoral areas. As these three policy approaches are applied in rangeland management and pastoral development worldwide, this paper may provide useful implications for future policy development in pastoral regions on a global scale.;  In China, three major rangeland management policies have caused dramatic social, economic, and ecological changes for pastoral regions in the past 30yr: the Rangeland Household Contract Policy (RHCP), Rangeland Ecological Construction Projects (RECPs), and the Nomad Settlement Policy (NSP). The impacts of these policies are greatly debated. In this paper, we conduct a systematic review of academic perspectives on the impacts of the three policies and the causes of ineffective and negative effects. The findings demonstrate that academics increasingly report negative impacts of RHCP on the ecosystem, animal husbandry, pastoralist livelihoods, and pastoral society. An increasing number of scholars, although not the majority, attribute the negative impacts to improper policy itself rather than incomplete implementation. Regarding the RECPs, most academics believe that policies have improved the rangeland ecosystem but with obvious negative impacts on pastoralist livelihoods and pastoral society; they attribute the problems to incomplete policy implementation. For the NSP, most academics report positive impacts on pastoralist livelihoods and animal husbandry, although recent researchers have identified negative impacts on pastoral society and the ecosystem. Although they are not in the mainstream, more and more academics attribute the negative impacts to improper policy. Finally, we apply the concept of coupled social-ecological systems (SES) to further analyze the outcomes of these three policies and propose a more flexible and inclusive land tenure policy that recognizes the diverse local institutional arrangements; an integrated RECP framework that considers coadaptation between social and ecological systems; and facilitating voluntary choice in nomad settlement and developing innovative approaches to provide social services for pastoralists who would like to remain in pastoral areas. As these three policy approaches are applied in rangeland management and pastoral development worldwide, this paper may provide useful implications for future policy development in pastoral regions on a global scale.;
Keywords: Animal husbandry; Breeding of animals; China; Coadaptation; Construction industry; Contracts; Councils; coupled social-ecological system; Debates; Degradation; ECOLOGY; Economics; ECOSYSTEMS; ENVIRONMENTAL SCIENCES; Farming; Households; Husbandry; INNER-MONGOLIA; Innovations; Livestock; Modernization; nomad settlement; Nomads; People's Rep; Project engineering; rangeland ecological restoration; rangeland management; rangeland tenure; Rangelands; Reviews; Social services; Society; STEPPE; SYSTEMS; WESTERN CHINA